2010
DOI: 10.1038/nature08971
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of optineurin in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) has its onset in middle age and is a progressive disorder characterized by degeneration of motor neurons of the primary motor cortex, brainstem and spinal cord. Most cases of ALS are sporadic, but about 10% are familial. Genes known to cause classic familial ALS (FALS) are superoxide dismutase 1 (SOD1), ANG encoding angiogenin, TARDP encoding transactive response (TAR) DNA-binding protein TDP-43 (ref. 4) and fused in sarcoma/translated in liposarcoma (FUS, also known as TLS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
880
2
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,126 publications
(932 citation statements)
references
References 21 publications
13
880
2
8
Order By: Relevance
“…In addition to this, heterozygous and homozygous OPTN mutations have been identified in patients affected with familial, middle‐age‐onset, Amyotrophic Lateral Sclerosis (ALS), a progressive disorder characterized by degeneration of motor neurons of the primary motor cortex (Maruyama et al. 2010; Maruyama and Kawakami 2013), including one study which identified a risk allele for OPTN ‐associated glaucoma in combination with a missense change in another ALS‐associated gene, raising the possibility of digenic inheritance (Weishaupt et al. 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, heterozygous and homozygous OPTN mutations have been identified in patients affected with familial, middle‐age‐onset, Amyotrophic Lateral Sclerosis (ALS), a progressive disorder characterized by degeneration of motor neurons of the primary motor cortex (Maruyama et al. 2010; Maruyama and Kawakami 2013), including one study which identified a risk allele for OPTN ‐associated glaucoma in combination with a missense change in another ALS‐associated gene, raising the possibility of digenic inheritance (Weishaupt et al. 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with a deletion (U31, U107, U187 and U198), the deletion points demonstrated the joining of the 5 0 part and 3 0 part with 1-to 8-base-pair microhomology (Figure 1a), which suggests the possibility that these deletions resulted from recombination with unequal crossover. 12 We first evaluated the cellular expression levels of the mutant proteins following forced expression in 293T cells. The result showed that exon deletions (DC185, D143-184, L240Q and DC376-441) and L240Q mutant expressed significantly less protein than did either the wild-type or I363M (Figure 1b, top, indicated by arrowheads), despite a similar level of expression of the corresponding mRNAs (Figure 1b, bottom).…”
mentioning
confidence: 99%
“…Optineurin (OPTN1) is an autophagy adaptor, whose mutations are linked to ALS (Maruyama et al, 2010;Del Bo et al, 2011). In addition to its roles of degradating foreign pathogens (xenophagy) (Wild et al, 2011) and binding to protein aggregates (Korac et al, 2013), OPTN1 is found in neuronal inclusions of patients affected by ALS and other neurodegenerative diseases (Schwab et al, 2012;Mori et al, 2012).…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%
“…The role of OPTN1 in ALS has been further elucidated by the recent discovery of loss of function mutations in TBK1 gene in familial ALS cases (Cirulli et al, 2015). The interaction between TBK1 and OPTN1 is a key factor in autophagy and inflammation (Maruyama et al, 2010;Maruyama and Kawakami, 2013;Thomas et al, 2013;Kachaner et al, 2012). TBK1 enhances the autophagic turnover of bacteria-bound ubiquitylated proteins (Wild et al, 2011;Gleason et al, 2011), through the phosphorylation of OPTN and SQSTM1 (Morton et al, 2008;Pilli et al, 2012) and promoting the interaction of OPTN with LC3.…”
Section: Accumulation Of Als Pathogenetic Proteins and Autophagymentioning
confidence: 99%